Perspektif Masyarakat terhadap Janji Pasangan Presiden Prabowo-Gibran dalam Pemberitaan di Tempo.Co dalam Sosial Media X - Elpira Pebrian; Peby Yanti; Daffa Isfalana; Raditya Cahya Rafif; Pia Khoirotun Nisa (Yayasan Pendidikan Penelitian Pengabdian Algero, 2024)
The aim of this research is to find out the public's perspective on the promises of the Prabowo-Gibran presidential couple in the news on Tempo.co on social media X. The researcher will discuss the public's response or perspective on a social media platform regarding the vision and mission of the presidential candidate candidate uploaded via the platform. This research also uses qualitative research with an approach through observation, interviews and literature study. Apart from observation, researchers also use the interview method which is the process of collecting data or information through face-to-face meetings between the questioner and the person being asked or answering. Apart from that, the researcher also used the library study method. With this method the researcher has observed, collected and recorded all data taken from comments on Tempo.Co posts, apart from that the researcher has also taken data obtained from answers by netizens when interviewed one by one. The reason why people are doubtful about the promises made by the Prabowo-Gibran presidential pair is because according to the public, these promises are still very difficult to realize with a relatively short term of office.